Beta blockade in lithium tremor. Issue 7 (July 1975) - Kellett, J M; Metcalfe, M; Bailey, J; Coppen, A J
Abstract : Practolol, propranolol, and placebo have been tested on an objective test of lithium induced tremor. Both beta-blocking agents produced significantly more tremor than the placebo. It is argued that lithium induced tremor is closer to essential than to physiological tremor.